Renoir [videorecording (DVD)] - Bourdos, Gilles, 1963-; Rottiers, Vincent; Bouquet, Michel; Théret, Christa; Doret, Thomas; Bohringer, Romane; Brandt, Carlo; Renoir, Jacques
Jean Renoir, son of the Impressionist painter Pierre-Auguste, returns home in the summer of 1915 to Southern France after being wounded in World War I and meets a young woman who inspires both himself and his father.